2020
DOI: 10.1182/bloodadvances.2020002566
|View full text |Cite
|
Sign up to set email alerts
|

Che-1/AATF-induced transcriptionally active chromatin promotes cell proliferation in multiple myeloma

Abstract: Multiple myeloma (MM) is a hematologic malignancy produced by a clonal expansion of plasma cells and characterized by abnormal production and secretion of monoclonal antibodies. This pathology exhibits an enormous heterogeneity resulting not only from genetic alterations but also from several epigenetic dysregulations. Here we provide evidence that Che-1/AATF (Che-1), an interactor of RNA polymerase II, promotes MM proliferation by affecting chromatin structure and sustaining global gene expression. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 59 publications
3
55
0
Order By: Relevance
“…As previously observed, Che-1 displayed to have a key role in MM cells proliferation (14). To assess whether this effect could also be observed in other tumor cells of different origins, we performed cell proliferation analysis in HCT116, HeLa, 293T and U2OS cells, depleted or not for Che-1 expression.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…As previously observed, Che-1 displayed to have a key role in MM cells proliferation (14). To assess whether this effect could also be observed in other tumor cells of different origins, we performed cell proliferation analysis in HCT116, HeLa, 293T and U2OS cells, depleted or not for Che-1 expression.…”
Section: Resultsmentioning
confidence: 65%
“…1D). It has been shown that Che-1 depletion produces a global reduction of histone acetylation in MM cells (14). To extend these ndings, we performed WB analyses in several tumor cell lines depleted or not for Che-1 expression, observing that the loss of Che-1 expression produced a strong reduction in both H3 and H4 histone acetylation (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations